KEBIJAKAN PIDANA KERJA SOSIAL DI INDONESIA SEBAGAI PIDANA ALTERNATIF DAN SOLUSI PROBLEM LEMBAGA PEMASYARAKATAN - Idul Adnan; Zulharman Zulharman; Lukman Hakim; Muhammad Sujudi (Journal of Law and Administrative Science, 2026)
Overcrowding or excess capacity in correctional institutions is a serious problem in the criminal justice system in Indonesia. One alternative that could be a solution is the application of social work punishment. Social work punishment offers a more humane approach and does not burden correctional institutions. Aim. This study aims to examine the policy of social work sanctions in Indonesia as an alternative sentencing approach and its potential as a solution to address the issues of overcrowding in correctional institutions. It explores the feasibility and effectiveness of implementing social work penalties within Indonesia’s legal framework, specifically in mitigating prison overcrowding and improving rehabilitation outcomes for offenders. Methods. The research employs a normative juridical approach by analyzing laws, regulations, and relevant literature related to criminal sanctions in Indonesia. In addition, qualitative data is gathered through interviews with legal practitioners, corrections officers, and policymakers to understand the perspectives and readiness of the criminal justice system to implement social work penalties. Comparative analysis with international practices is also included to evaluate the adaptability and potential challenges in Indonesia. Results. Findings reveal that social work penalties can serve as an effective alternative to custodial sentences for non-violent offenders, reducing the burden on correctional facilities. Implementation challenges include the need for regulatory support, coordination among institutions, and public awareness. Nevertheless, social work sanctions show promise in promoting rehabilitative justice, lowering recidivism, and creating a more balanced criminal justice system in Indonesia.